A Dictionary of Nursing - Editor Martin, Elizabeth A. (Oxford ; New York Oxford University Press, 2014)
This best-selling Dictionary provides comprehensive and authoritative coverage of all aspects of nursing. The new edition has been fully updated and revised to take account of developments in nursing practice and related fields. New coverage includes recent legislation such as the Mental Capacity Act, and developing areas such as quality of life and nurse-led clinics. The Dictionary provides comprehensive treatment of the ever-expanding vocabulary of the nursing professions. In addition to specific nursing terms, there are many entries in the fields of medicine, anatomy, physiology, psychiatry, nutrition, and pharmacology (including new drugs recently introduced into medical practice). Written by medical and nursing specialists, this trusted dictionary covers the theory and practice of nursing, and includes up-to-date entry-level web links. The text is enhanced by over 100 helpful illustrations and tables. This is an invaluable reference tool for all nursing students, recently qualified and practising nurses, and people training and working in related fields such as midwifery and health visiting
Include Appendix
Keywords: Nursing -- Medicine